Pengaruh Kebijakan Pemerintahan Kota Padang terhadap Perubahan Akhlak dan Moral Peserta Didik melalui Program Smart Surau - Nabil Eka Saputra; Muhammar Hasbi Asidiq; Gusmaneli (JDP (JURNAL DINAMIKA PENDIDIKAN), 2025)
This study aims to analyze the influence of the Padang City Government’s policy on students’ moral and character development through the Smart Surau program. This program is a religious-based character education innovation developed by the local government to strengthen students’ spiritual, social, and moral values. The research method used is quantitative with a descriptive and verificative approach. Data were collected through questionnaires distributed to students participating in the Smart Surau program and interviews with school representatives and program managers. The findings show that government policy has a significant influence on improving students’ morals and character. The Smart Surau program has proven effective in fostering religious attitudes, discipline, responsibility, and social awareness. Therefore, this policy can serve as a model for developing Islamic value-based character education in other regions.